The role of autophagy in periodontal diseases: a bibliometric analysis from 2006 to 2023 - Zhang, Bitong; Wang, Yahui; Chang, Haoxiang; Wang, Chong; Fan, Hong; Ren, Xiuyun (Frontiers in Medicine, 2025)
BackgroundPeriodontal disease is a chronic inflammatory condition affecting the supporting structures of the teeth, involving complex interactions between systemic and local immune responses. Autophagy is a tightly regulated cellular process that is responsible for degrading and recycling cellular components, playing a pivotal role in maintaining cellular homeostasis and modulating inflammation in periodontal disease. In recent years, the relationship between these two factors has attracted attention from scholars globally. However, bibliometric analyses in this field are still limited.ObjectivesTo analyze the bibliometric trends and research hotspots related to the role of autophagy in periodontal disease.MethodsArticles and reviews examining the association between periodontal disease and autophagy were retrieved from the Web of Science Core Collection (WOSCC) on 20 June 2024. Bibliometric and knowledge mapping analyses were performed using CiteSpace [6.3. R1 (64-bit) Advanced].ResultsThrough a bibliometric analysis of literature published between 2006 and 2023 on the role of autophagy in periodontal disease, 341 relevant studies were identified. The results indicate a steady annual increase in studies on this topic, with a significant upward trend observed post-2015. Keyword analysis identifies “apoptosis,” “Porphyromonas gingivalis,” “oxidative stress,” “inflammation,” “periodontitis,” “osteogenic differentiation,” “cell death,” and “orthodontic tooth movement” as key research hotspots. Collaboration network analysis identifies China as the leading contributor to research in this field. Document co-citation analysis highlights several influential studies examining the “double-edged sword” role of autophagy in periodontal disease, illustrating how autophagy alleviates oxidative stress and inflammation in periodontitis by removing damaged organelles, inhibiting pro-inflammatory mediators, and promoting periodontal tissue repair through the secretion of pro-angiogenic cytokines. However, excessive autophagy may lead to apoptosis when cellular stress surpasses the repair capacity. This study identifies key trends and research hotspots in autophagy and periodontal disease, underscoring the importance of international collaboration and high-impact journals for advancing the field and guiding future research.ConclusionRecent studies indicate that autophagy has emerged as a critical mediator with dual roles in periodontal disease. Therefore, early control of periodontal inflammation, along with the exploration of how to harness the protective functions of autophagy, may provide future research directions for managing periodontal disease.